Relationship between Level of Knowledge and Anxiety Facing Menopause in Women in Karang Pule Village, West Nusa Tenggara, Indonesia - Arieska, Risa (Archives of The Medicine and Case Reports, 2024)
Significant hormonal changes during menopause can influence emotional and physical well-being. Some women experience anxiety due to hormonal changes that can influence mood, sleep, and energy. This study aims to describe the level of knowledge and anxiety about facing menopause in women in Karang Pule village, West Nusa Tenggara, Indonesia. This research is an observational study with a cross-sectional design. The research was carried out in August-November 2023 at the Integrated Development Post (Posbindu) in Karang Pule village, Mataram, West Nusa Tenggara, Indonesia. Participants in this research were menopausal women in Karang Pule village. The inclusion criteria for participants were women aged over 40 years, had experienced menopause, and were willing to be respondents. A total of 42 women took part in this study. The majority of female respondents in Karang Pule village have a high school education (47.62%), have sufficient knowledge (52.40%), and experience moderate anxiety (71.42%). There is a relationship between the level of maternal knowledge about menopause and the level of anxiety during menopause in Karang Pule village (p<0.05). A coefficient correlation value was also obtained -0.425, which means that the better the mother's knowledge about menopause, the lower the anxiety experienced. In conclusion, there is a relationship between the level of knowledge and the level of anxiety during menopause among respondents in Karang Pule Village.